PEMIKIRAN FIQH DAN TASAWWUF SYEKH MUHAMMAD NAWAWI BANTEN DAN PENGARUHNYA TERHADAP MODERASI BERAGAMA DAN PERDAMAIAN - Ahmad Muzakki (LP2M Universitas Ibrahimy, 2020)
Syekh Muhammad Nawawi Banten is a figure of the Indonesian Ulama who has a major contribution in Islamic law and the formation of national character. His works cover various disciplines. Syekh Nawawi is one of the scholars who are able to combine science of jurisprudence and tasawwuf. In his Sufi fiqh thinking there are a number of moderation values that affect peace. This study uses literature and conceptual studies. The values of moderation in fiqh thinking include always trying to minimize differences of opinion, tolerant in the midst of differences of opinion madzhab, be careful (ihtiyath) in setting the law, and not fanatic madzhab. While among moderate thoughts in Sufism is the teaching about the combination of Shari'a, Tariqot and the nature, between tawakkal and endeavor in seeking income. The values of moderation in the thought of fiqh and tasawwuf Shaykh Nawawi Banten are very influential in shaping the nation's character and creating peace. This can be seen from the moderate thinking of his students who have extraordinary influence in Indonesia. The thought of fiqh and Sufism Shaykh Nawawi can foster tolerance, mutual respect amid differences, enthusiasm for work and discipline in all activities.